Tax Policy Issues in Designing a Carbon Tax - Marron, Donald B.; Toder, Eric J. (American Economic Review, 2014)
A carbon tax is a promising tool for discouraging the greenhouse gas emissions that cause climate change. In principle, a well-designed tax could reduce the risk of climate change, minimize the cost of emissions reductions, encourage innovation in low-carbon technologies, and raise new public revenue. But designing a real-world carbon tax poses significant challenges. We analyze those challenges from a public finance perspective, emphasizing three tax policy design issues: setting the tax rate, collecting the tax, and using the resulting revenue. The benefits of a carbon tax will depend on how policymakers address those issues.